2018
DOI: 10.12688/wellcomeopenres.14767.2
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory validation and field usability assessment of a point-of-care test for serum bilirubin levels in neonates in a tropical setting

Abstract: Background: Screening and monitoring serum bilirubin (SBR) in neonates is crucial to prevent neonatal hyperbilirubinemia (NH)-associated morbidity and mortality worldwide. A lack of resources is often a barrier for measuring SBR in developing countries. Reliable, cost-effective, easy to use point-of-care (POC) SBR tests are needed. This study aimed to evaluate the technical accuracy and usability of the Bilistick System (BS), a new bilirubin POC test, in a tropical setting. Methods: This was a mixed-methods st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 33 publications
(39 reference statements)
0
11
0
Order By: Relevance
“…The studies reported a total of 3122 paired measurements. Of the 10 included studies, 8 studied the Bilistick (Bilimetrix srl), a POC test for total bilirubin quantification in 25 μL of whole blood . The Bilistick consists of a handheld reflectance reader and test strips, which are composed of a blood-plasma filter and nitrocellulose membrane.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The studies reported a total of 3122 paired measurements. Of the 10 included studies, 8 studied the Bilistick (Bilimetrix srl), a POC test for total bilirubin quantification in 25 μL of whole blood . The Bilistick consists of a handheld reflectance reader and test strips, which are composed of a blood-plasma filter and nitrocellulose membrane.…”
Section: Resultsmentioning
confidence: 99%
“…The reported percentage of failed quantifications of the Bilistick varied between 1.5% and 48.6% across studies, with a median of 8.75% (IQR, 5.02%-24.07%) . Common error messages were high hematocrit (>65%) and hemolysis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations